2019
DOI: 10.1111/nrm.12211
|View full text |Cite
|
Sign up to set email alerts
|

Optimal harvest strategy for even‐aged stands with price uncertainty and risk of natural disturbances

Abstract: We present a reservation price model to examine the joint impacts of natural disturbances and stumpage price uncertainty on the optimal harvesting decision for even‐aged forest stands. We consider a landowner who manages a loblolly pine stand to produce timber and amenities, under age‐dependent risk of wildfires and uncertainty in future timber prices. We show that the incorporation of risk of wildfires decreases the optimal reservation prices. The inclusion of risk of wildfires leads to lower land values and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Previous research investigating the effect of catastrophic events on the optimal rotation age, such as Reed (1984) and Susaeta and Gong (2019), advocates for shortening the rotation length as the best management option to maximize the value of the stand. Also, Macpherson et al (2016) show that under a risk of a pathogenic disease outbreak that would make the timber of trees affected by it worth nothing, shortening the rotation length is the optimal strategy for managing the land.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research investigating the effect of catastrophic events on the optimal rotation age, such as Reed (1984) and Susaeta and Gong (2019), advocates for shortening the rotation length as the best management option to maximize the value of the stand. Also, Macpherson et al (2016) show that under a risk of a pathogenic disease outbreak that would make the timber of trees affected by it worth nothing, shortening the rotation length is the optimal strategy for managing the land.…”
Section: Discussionmentioning
confidence: 99%
“…Reed (1984) adapted the Faustmann formula for infinite rotation to consider wildfire risk using a homogeneous Poisson distribution. Susaeta and Gong (2019) also investigated the risk of natural disasters by incorporating it into a reservation price model. Díaz-Yáñez et al (2019) looked into how the risk of snow and wind damage can impact the harvesting ages in spruce forests in Norway.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Susaeta and Gong (2019) employ a reservation price model to estimate the joint impacts of natural disturbance and stumpage price uncertainty on the optimal harvesting decision for even-aged forest stands. The authors suggested that forest owners should consider the wildfire risk and market price simultaneously when determining the optimal harvesting decision.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Susaeta and Gong () investigate the effects of two risk components (price and wildfire) on the even‐aged forest land. Using the reservation price model, they show that wildfire risk reduces the optimal reservation price, hastens the harvesting of trees, and provides lower land values.…”
mentioning
confidence: 99%
“…For example, Fuglie and Heisey (2007) indicate that public investment in U.S. agriculture has increased crop outputs, and this has benefitted farmers (increased revenue) and consumers (availability of food in an affordable price). Susaeta and Gong (2019) investigate the effects of two risk components (price and wildfire) on the even-aged forest land. Using the reservation price model, they show that wildfire risk reduces the optimal reservation price, hastens the harvesting of trees, and provides lower land values.…”
mentioning
confidence: 99%